Development of a theory-based intervention to increase cognitively able frail elders' engagement with advance care planning using the behaviour change wheel - S. Combes; G. Forbes; K. Gillett; C. Norton; C. J. Nicholson (BMC, 2021)
Abstract Background Advance care planning (ACP) conversations support people to think about, discuss and document their beliefs, values and preferences regarding future care. This process means that should the person loose capacity in the future, care can be provided, consistent with their personal values and beliefs. The ACP process is particularly relevant for older people living with frailty (frail elders) as they are vulnerable to sudden deterioration. However, ACP is rarely undertaken by frail elders. The aim of this study was to develop an intervention to increase multidisciplinary health and social care professionals' (H&SCPs) engagement of cognitively able, domestic-dwelling frail elders with ACP. Methods Intervention development was guided by the Medical Research Council framework for complex interventions and the Behaviour Change Wheel. Multiple methods were used to understand ACP barriers and enablers: a systematic integrative review, a survey (n = 73 H&SCPs), and semi-structured interviews (n = 10 frail elders, n = 8 family members). A conceptual model, developed from the integrative review, underpinned data collection for the survey and interviews. Synthesis of this data, including patient and public involvement, was then used to identify H&SCPs behaviours that needed to change for ACP to be implemented and decide content and implementation for the intervention. Results Following the Behaviour Change Wheel system, and based on the findings of the review, survey and interviews, the prototype intervention, Conversations on Living and Dying (CLaD), was developed. The CLaD prototype consisted of one 3.5-hour educational skills session for H&SCPs supported by a toolkit. Content focussed on the relevance of ACP for frail elders, experience of ACP by frail elders, and strategies H&SCPs could adopt to encourage frail elders' engagement with ACP. Strategies include recognising the importance of relationships and living well now, preparing frail elders for ACP conversations and starting ACP early. Participants who took part in initial prototype refinement reported that the intervention helped them think differently about ACP and encouraged them to engage with frail elders. Conclusions The use of behavioural theory enabled the development of CLaD, an evidence-based, theory-driven, person-centred intervention to support ACP engagement with frail elders. While feasibility testing is required, initial prototype refinement demonstrated that H&SCPs found the intervention to be acceptable, engaging, and clinically valuable in their practice with frail elders and their families.